Bezzałogowe statki powietrzne w przestępczości. Część I: Kwestie terminologiczne, wątpliwości prawne i postulaty zmian - Kryński, Marcin (PRAWO i WIĘŹ, 2025)
The aim of the paper is a legal-dogmatic analysis of prohibited acts committed using drones in the context of selected legal regulations in aviation law, contained in the Act of 3 July 2002 - Aviation Law, as well as certain international laws. The research employs the dogmatic method, literature analysis, and a review of current case law. The paper attempts to address terminological dilemmas concerning drones and examines prohibited acts defined in the Aviation Law from the perspective of the still ongoing interpretative challenges. The conducted research has led to conclusions and the formulation of de lege ferenda postulates, outlined in the summary, whose incorporation into the current legislation should be considered.